Classics and prison education in the US - Capettini, Emilio; Rabinowitz, Nancy Sorkin (Classics in and out of the academy classical pedagogy in the twenty-first century, 2021)
Introduction /Emilio Capettini, Nancy Sorkin Rabinowitz --Part 1: Old texts, new classrooms.Reading the emotions inside and outside: classical Greek texts in prison and beyond /Emily Allen-Hornblower --"Because we've done bad things" : reading the Homeric hymn to Demeter in prison /Elizabeth Bobrick --Dialogic pedagogy as a model for teaching classics in prison /Nancy Felson, Nebojša Todorović --Surmises and surprises : notes on teaching ancient Greek literature in a correctional facility /Amy E. Johnson, Laura M. Slatkin --Inside out : classical myth in a county jail /Alexandra Pappas --From family violence to civic order : ancient myths and modern theory in a medium security prison /Stephen Scully --